2022
DOI: 10.1111/1750-3841.16291
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and morphological characteristics of potato pectin with in‐situ acid‐induced gelation

Abstract: Pectin in the potato cell wall plays an important role in strengthening connections of intercellular junctions during thermal processing through in-situ acid-induced gelation (in-situ acid-induced gelation [AIG]). Thus, the variation in the physicochemical and structural characteristics of potato pectin with in-situ AIG was focused in this study. The intra-and intermolecular hydrogen bonding among (d-galacturonic acid) GalA units around 3400 cm -1 (absorbance intensity was increased from 50.9 to 70.7) in Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These techniques have elevated the extraction efficiency of potato pectin by directly destroying the linkages among pectin, hemicellulose, and cellulose, accompanied with the destruction of the pectin structure. Recent research has revealed that original pectin in potato cell walls could participate in maintaining the cell structure during food processing [ 14 , 15 , 16 ]. It was found that the acid-induced in situ gelation of pectin in the cell wall played a role in the significant increase in the hardness of cooked potato slices.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have elevated the extraction efficiency of potato pectin by directly destroying the linkages among pectin, hemicellulose, and cellulose, accompanied with the destruction of the pectin structure. Recent research has revealed that original pectin in potato cell walls could participate in maintaining the cell structure during food processing [ 14 , 15 , 16 ]. It was found that the acid-induced in situ gelation of pectin in the cell wall played a role in the significant increase in the hardness of cooked potato slices.…”
Section: Introductionmentioning
confidence: 99%